2020
DOI: 10.1146/annurev-environ-012220-105152
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Contamination of Drinking Water in Resource-Constrained Settings: Global Prevalence and Piloted Mitigation Strategies

Abstract: Chemical contamination of drinking water (including salinity) puts more than one billion people at risk of adverse health effects globally. Resource-constrained communities are the most affected and face unique challenges that require innovative safe water solutions. This review focuses on arsenic, fluoride, nitrates, lead, chromium, total dissolved solids, emerging organic contaminants, and, to a lesser extent, manganese, cadmium, selenium, and uranium. It covers contaminant prevalence, major health effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 170 publications
(250 reference statements)
0
21
0
Order By: Relevance
“…Poor institutional, regulatory and management aspects have also led to poor catchment management thus resulting in pollution (Afroz et al 2014). Polluted water sources pose a major challenge during potable water treatment (Dlamini et al 2016 including increased costs of treatment (Amrose et al 2020) and risks of water borne diseases due to poor drinking water quality (Praveen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Poor institutional, regulatory and management aspects have also led to poor catchment management thus resulting in pollution (Afroz et al 2014). Polluted water sources pose a major challenge during potable water treatment (Dlamini et al 2016 including increased costs of treatment (Amrose et al 2020) and risks of water borne diseases due to poor drinking water quality (Praveen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These include chemical (e.g., chlorination) [3], physical (e.g., filtration) [50,51], and thermal treatment methods (e.g., boiling, pasteurization) [29], and a combination thereof [40,52]. However, considering the increasing universal use of chemicals including those of emerging health concern (e.g., pharmaceuticals and personal care products), it has been recently demonstrated that contamination by synthetic chemicals is increasingly of worldwide concern [32,53,54]. This is in addition to well-known toxic geogenic contaminants such as radionuclides (e.g., U), arsenic, and fluoride, among others.…”
Section: Community-scale Safe Drinking Water Supplymentioning
confidence: 99%
“…Consequently, decentralized safe drinking water systems should address both biological and chemical contamination [32,52,53]. Moreover, the quality of treated water should be assessed (or confirmed) using instrumental water analysis [54,[56][57][58]. This calls for a shift in the present paradigm in developing countries that places emphasis on the water supply (e.g., via drilling of boreholes) with limited consideration for the analytical testing and treatment of such water.…”
Section: Community-scale Safe Drinking Water Supplymentioning
confidence: 99%
“…Chemical contamination of water is a substantial threat to human health and safety, and is expected to have impacts that are more significant in the upcoming decades. According to Amrose et al [22], the impacts of chemical contamination on humans may increase, mainly due to increasing industrialization and climate change. The most common chemical contaminants that affect the quality of water are the following:…”
Section: Chemical Contamination Of Watermentioning
confidence: 99%